Legal Validity Of Butonese Customary Collective Agreement Agreement On Land Use As Limestone Mine (Case Study Of PT. Diamond Alfa Propertindo With The Indigenous People Of Gumanano Village, Central Buton Regency) - Rusman, Rusman (Universitas Islam Malang, 2024)
Abstract : Indonesia is one of the countries that has thousands of islands, so each region has its own tribe and culture. The customary law of each region is different but still one under the auspices of the Indonesian state. Customary law is recognized, respected and protected by the state as long as it is still in accordance with the times as stated in articles 18B paragraph (2) and 28I paragraph (3) of the 1945 NRI Constitution. The purpose of this study is firstTo describe and analyze the legal validity of the Butonese customary agreement on land use as a limestone mine by PT. Diamond Alfa Propertindo second, To describe and analyze the legal consequences of customary buton agreements on the use of land as limestone mines by PT. Diamond Alfa Propertindo. The research method used is juridical Sociology with an approach to concepts and laws and regulations. The results of research and discussion show that first the validity of the agreement according to the western legal system based on the Civil Code Article 1320 which states that for the validity of the agreement 4 conditions are needed, namely, Agree they bind themselves, Ability to make an agreement, A certain thing, A lawful cause. while the validity of the contract according to Islamic Law must fulfill the pillars of the pillars, namely, Sighat al-aqad (declaration to bind oneself), Al-ma'qud alaih or Mahal alaqd (object of contract), Al-muta'aqidain or al-aqidain (contracting parties), Maudhu' al-aqd (purpose of contract). And the Validity of the Agreement according to Customary Law, namely, Adult or capable, the Principle of Agreement, the provisions that accompany the agreement but are not the validity of the agreement according to customary law. So it can be concluded that the customary agreement on the use of land as a limestone mine by PT.Diamond Alfa Propertindo i.e. legitimate. Both in review of customary law, Islam and the Civil Code. Both lands used for limestone mining are customary lands. To protect land rights in mining, there is an MoU and CSR. If in mining 86 there are irregularities committed by business actors, then the business license from the mining will be revoked.Keywords: Legal validity, Customary Agreement, and Land Use